Establishing a Data-Sharing Environment for a 21st-Century Academic Health Center - Khurshid, Anjum; Rousseau, Justin F.; Andrews, Steven B.; Tierney, William M. (ACI Open, 2020)
Objective The main purpose of this study was to establish a seamless clinical data sharing system in a new medical school in partnership with community health systems.Methods We developed a Data Request Management System (DRMS) and a data request process to streamline access to and management of data for quality improvement, population health, and research. We utilized a four-pronged methodology in implementing our clinical data sharing system: data governance, data extraction, external relationships, and internal engagement.Results The Data Core team of honest data brokers through the established relationships, data use agreements, data request processes, and the DRMS processed more than 50 data requests from all the departments during its first year of operation. The DRMS application and the supporting governance and relationships provided a platform for improved process and accuracy of data sharing environment by facilitating trust, transparency, standardization, and service provisioning.Conclusion Developing a seamless data ecosystem that forms the basis of a learning health system between an academic health center and community health systems requires a combination of people (the Data Core team), processes (common data request process policies and procedures), and technology (an effective online DRMS). Future work is needed to measure the impact of the clinical data sharing system on efficiency and accuracy of data sharing.
Keywords: data sharing; data governance; electronic health record